Principles of green bioethics : sustainability in health care - Richie, Cristina (Michigan State University Press, 2019)
Health care is ubiquitous in the industrialized world. Yet, every medical development, technique, and procedure impacts the environment. Green bioethics synthesizes environmental ethics and biomedical ethics, thus creating an interdisciplinary approach to sustainable health care. Notably, green bioethics addresses not the structure of environmental sustainability in health-care institutions but the sustainability of individual health-care offerings. It parallels traditional biomedical ethics by providing four principles for ethical guidance: distributive justice, resource conservation, simplicity, and ethical economics. Through these four principles, green bioethics presents a coherent framework for evaluating the sustainability of medical developments, techniques, and procedures. The future of our world may very well depend on how effectively we halt ecological destruction and conserve our resources in all areas of life. The principles of green bioethics, outlined in this book, will advance sustainability in health care.